2010
DOI: 10.1007/s12011-009-8599-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Fluorine on the Cell Cycle and Apoptosis of Renal Cells in Chickens

Abstract: The experiment was conducted with the objective of evaluating the effect of dietary high fluorine (F) on cell cycle and apoptosis of kidney in chickens by the methods of flow cytometry. Three hundred 1-day-old Avian broilers were divided into four groups and fed on control diet (F 23 mg/kg) and high F diets (400 mg/kg, high F group I; 800 mg/kg, high F group II; 1,200 mg/kg, high F group III) for 6 weeks. As tested by flow cytometry, the percentage of renal cell apoptosis was increased with increasing of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 11 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…Many of these cellular events ultimately lead to cell death. NaFinduced apoptosis was demonstrated in the cells from different organs and tissues including lungs [25,26], kidneys [27,28], liver [29][30][31], brain [32][33][34], pancreas [35,36], thymus [37], endometrium [38,39], bone marrow [40], hair follicles [41], erythrocytes [42][43][44], as well as leukemic cells [45][46][47].…”
Section: Fluoride-induced Toxicity and Cell Deathmentioning
confidence: 99%
“…Many of these cellular events ultimately lead to cell death. NaFinduced apoptosis was demonstrated in the cells from different organs and tissues including lungs [25,26], kidneys [27,28], liver [29][30][31], brain [32][33][34], pancreas [35,36], thymus [37], endometrium [38,39], bone marrow [40], hair follicles [41], erythrocytes [42][43][44], as well as leukemic cells [45][46][47].…”
Section: Fluoride-induced Toxicity and Cell Deathmentioning
confidence: 99%
“…Fluoride toxicity targets to not only bone and teeth, but also soft tissues [6]. Previous studies have proved that fluorine can induce genotoxicity, cytotoxicity, immunotoxicity, oxidative damage, apoptosis and lesions in the broiler peripheral blood [7–10], liver [11, 12], kidney [13–15], thymus [16], spleen [17–19], bursa of Fabricius [20], cecal tonsil [21–25], and intestine [2630], and in the mouse spleen and kidney [3135]. …”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, Zhang et al (2008) demonstrated that F (40 or 80 ppm) induced S-phase cell cycle arrest and DNA damage in primary cultured rat hippocampal neurons. Bai et al (2010) reported G0/G1 arrest in chicken renal cells at high F concentrations. In agreement with Barbier et al (2010), F arrested the cell cycle at various phases of the cell cycle progression depending upon the concentrations and cell types tested.…”
mentioning
confidence: 99%